KAJIAN STUDI LITERATUR: IMPLEMENTASI PROGRAM LINK AND MATCH TERHADAP DAYA SERAP LULUSAN SMK DI INDUSTRI - Irwanto Irwanto (Perkumpulan Dosen Program Hibah Indonesia, 2025)
Vocational education plays a strategic role in producing skilled workers ready to compete in the industrial, business, and employment sectors (IDUKA). The link-and-match program is a government initiative aimed at enhancing the relevance of vocational education to labor market demands. This study seeks to analyze the impact of the link-and-match program on the employability of vocational high school (SMK) graduates through a literature review method. The analysis reveals that the program's implementation, which involves collaboration between SMK and IDUKA, competency-based curriculum development, internships, and skill certification exams, positively influences graduates' readiness for the workforce. However, challenges such as student preparedness, limited facilities, and insufficient commitment from IDUKA remain significant obstacles. Proposed strategies include strengthening industry-based curricula, intensive teacher training, and enhancing partnerships with IDUKA. With stronger synergy among stakeholders, this program holds substantial potential for producing competent SMK graduates aligned with labor market needs in the era of Industry 4.0.